ROLE OF GREEN HUMAN RESOURCE MANAGEMENT IN THE GROWTH OF AN ORGANIZATION - Devi, Maya; Kuldeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Environment friendly policies and actions are being highly stressed all across the world. This study has highlight concerns about the role of green human resource management in an organization. The purpose of this paper is to examine the impact of GHRM on employees and their behavior. Green Human Resource Management literature and investigates the future of green practices in meeting the social sustainability requirements of an organization. Considering the growing awareness on greening sustainability. To save the earth, the whole business world is reciting the old motto of three R means: Reduce, Reuse and Recycle. The HRM structure of an organization should represent wealth, growth, well being, and health of internal and external. This study explores the success rate of implementing Green Human Resource Management practices in Indian Organizations.